2016
DOI: 10.1098/rsos.160839
|View full text |Cite
|
Sign up to set email alerts
|

Evolving interactions between diazotrophic cyanobacterium and phage mediate nitrogen release and host competitive ability

Abstract: Interactions between nitrogen-fixing (i.e. diazotrophic) cyanobacteria and their viruses, cyanophages, can have large-scale ecosystem effects. These effects are mediated by temporal alterations in nutrient availability in aquatic systems owing to the release of nitrogen and carbon sources from cells lysed by phages, as well as by ecologically important changes in the diversity and fitness of cyanobacterial populations that evolve in the presence of phages. However, ecological and evolutionary feedbacks between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 67 publications
0
24
1
Order By: Relevance
“…We have here shown that cyanophages have a different beta diversity in hypoxic-anoxic sediment compared to oxic, and are actively infecting cyanobacteria triggering the CRISPR/Cas system. We observed cyanobacterial N 2 xation in the hypoxic-anoxic sediment, and it is therefore likely that viral lysis of these cells contribute carbon, phosphorus, and nitrogen to other microorganisms [33,34]. The bacterial uptake of lysed material has been shown to be especially important in oligotrophic environments were nutrients are scarce [52], and this further suggests that viruses might have an important role in the studied dead zone sediments as they have been shown to be low or depleted in nitrate [43].…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…We have here shown that cyanophages have a different beta diversity in hypoxic-anoxic sediment compared to oxic, and are actively infecting cyanobacteria triggering the CRISPR/Cas system. We observed cyanobacterial N 2 xation in the hypoxic-anoxic sediment, and it is therefore likely that viral lysis of these cells contribute carbon, phosphorus, and nitrogen to other microorganisms [33,34]. The bacterial uptake of lysed material has been shown to be especially important in oligotrophic environments were nutrients are scarce [52], and this further suggests that viruses might have an important role in the studied dead zone sediments as they have been shown to be low or depleted in nitrate [43].…”
Section: Discussionmentioning
confidence: 59%
“…Cyanophages are viruses that are known to infect cyanobacteria and after infection lytic cyanophages eventually lyse the host cell [30][31][32], and thus contribute to the release of carbon and nutrients into the environment [33,34]. Furthermore, cyanophages might increase the decay of pelagic cyanobacteria and increase the amount sinking down towards the seabed through increased particle formation caused by viral lysis [35].…”
Section: Introductionmentioning
confidence: 99%
“…Both strains had been successfully cultured under similar conditions previously (Cairns et al. , Coloma et al. ).…”
Section: Methodsmentioning
confidence: 98%
“…Recently, we demonstrated that phage resistance evolution can alter phage‐mediated nitrogen release in filamentous cyanobacterial populations but potential larger, community‐level effects remain unclear (Cairns et al. , Coloma et al. ).…”
Section: Introductionmentioning
confidence: 99%
“…Cyanophages are viruses that are known to infect cyanobacteria and after infection lytic cyanophages eventually lyse the host cell [32][33][34], and thus contribute to the release of carbon and nutrients into the environment [35,36]. Furthermore, cyanophages might increase the decay of pelagic cyanobacteria and increase the amount sinking down towards the seabed through increased particle formation caused by viral lysis [37].…”
Section: Introductionmentioning
confidence: 99%